Predictors of Diffuse In-Stent Restenosis, a Retrospective Analysis in a Subset of Egyptian Population - El Amrawy, Ahmed Mahmoud; Loutfi, Mohamed Ibrahim; Abd El Azeem, Ahmed Mokhtar (Jurnal Kardiologi Indonesia, 2024)
Background: Despite the fact that DES implantation has decreased theincidence of ISR dramatically, it is not negligible. Diffuse ISR is associated withpoor outcomes. Most of the data regarding ISR are obtained from studiesincluding BMS stents. Methods: A total of 263 ISR patients were treated at two tertiary carehospitals from September 2017 through December 2022. 40 patients wereexcluded because the previous angiography and procedure details were notavailable, IVUS data were available for only 30 patients and the patients werenot included in the analysis, so only 193 ISR patients were included in theanalysis. We compared different clinical and procedural risk factors betweendiffuse and focal patterns of ISR following DES implantations. Results: A total of 193 ISR lesions were included in the analysis, distributedas 53.4% diffuse pattern and 46.6% focal pattern. In the multivariate analysis,only increased stent length [OR 1.270 (1.157 – 1.394) 95%CI, P<0.001],lower LVEF [OR 0.903, (0.860 – 0.949) 95%CI, P<0.001], occurrence ofprocedural complications [OR 15.584 (2.075 – 117.044) 95%CI, P=0.008],smoking [OR 3.182, (1.071 – 9.451) 95%CI, P=0.037] and older age [OR1.086, (1.014 – 1.163) 95%CI, P=0.019] were independent risk factors ofdiffuse ISR. DM was not associated with diffuse ISR in the multivariate analysis. Conclusions: Increased age, smoking, reduced left ventricular ejectionfraction, occurrence of procedural complications and increased stent lengthare independent predictors of diffuse ISR. Diabetes mellitus was not found tobe independently associated with a diffuse pattern of ISR.